Ecology of desert systems - Whitford, W. G. (Walter G.), 1936- (Academic Press, 2002)
Conventional wisdom considers deserts stark, harsh regions that support few living things. Most people also believe that water alone makes the desert bloom. Ecology of Desert Systems challenges these conventional views. This volume explores a broad range of topics of interest to ecosystem, population, community, and physiological ecologists. Climate, weather patterns, geomorphology, and wind and water processes are examined as variables that affect the distribution of biota through fundamental ecosystem processes. Descriptions of morphological, behavioral, and physiological adaptations of desert biota illuminate, through the lens of patch dynamics, principles for understanding observed patterns of primary production, nutrient cycling, and the effects of consumers. Desertification, and the techniques for monitoring and quantifying it, is examined within the framework of desert ecosystem patterns and processes. * Focuses on the interactions of climate, soil, and biota along a spectrum of spatial and temporal scales * Details the role of animals in desert ecosystems and landscape processes * Examines watershed scale processes, the ecology of ephemeral lakes, and the ecological changes identified with desertification * Outlines the fundamental concepts relevant to sustainable development of arid lands.